Testicular function and fertility outcomes in males with CF: A multi center retrospective study of men with congenital bilateral absence of the vas deferens based on CFTR mutation status - Rossella Cannarella; Danielle Velez Leitner; Marissa Weiss; Sarah C. Vij (Journal of Clinical & Translational Endocrinology)
Background: Modern cystic fibrosis (CF) treatments, particularly CFTR modulators, have allowed males with CF (MwCF) to live longer, healthier lives and pursue parenthood. Approximately 98% of MwCF have congenital bilateral absence of the vas deferens (CBAVD). While research shows MwCF experience spermatogenic dysfunction alongside obstructive azoospermia, understanding male reproductive health in MwCF remains limited. This study retrospectively examines testicular function and intracytoplasmic sperm injection outcomes of the partners of males with CBAVD, stratified by CF mutation status (CF, CF carriers, no known mutation). Subjects and Methods: This multicenter, retrospective study assessed sperm retrieval outcomes and testicular function in males with CBAVD. Participants were categorized into three groups: MwCF (Group 1), CFTR gene mutation carriers (CFTR carriers, Group 2), and CBAVD males without CFTR mutations (Group 3). We collected data on genetic testing, testicular hormone levels (FSH, LH, total testosterone), sperm retrieval methods, and reproductive outcomes. Statistical analysis was used to assess intergroup differences. Results: Thirty subjects were included (Group 1: 14, Group 2: 11, Group 3: 5). No significant differences in demographic, anthropometric, or reproductive characteristics were found across groups. Hormone levels (LH, FSH, and testosterone) were similar among groups. In Group 1, 42 % had elevated FSH levels. The prevalence of hypogonadism was 16.7 % in Group 1. Group 3 had a significantly lower fertilization rate (p < 0.01), but no differences were found in blastocyst formation, pregnancy, miscarriage, or live birth rates. Conclusions: Our data support the presence of primary spermatogenic dysfunction in some MwCF. However, reproductive outcomes were similar across all groups.